Birth Hospital and Racial and Ethnic Differences in Severe Maternal Morbidity in the State of California. Issue 4 (22nd December 2021) - Mujahid, M.S.; Kan, P.; Leonard, S.A.; Hailu, E.M.; Wall-Wieler, E.; Abrams, B.; Main, E.; Profit, J.; Carmichael, S.L.
Abstract : ( Am J Obstet Gynecol . 2021;224:219.e1–15) A persistent difference in the rate of severe maternal morbidity (SMM) continues to exist between White women and those of other racial and ethnic groups. This is especially true for Black women, who are up to 3 times more likely to experience SMM than White women. The factors underlying this inequity are unclear. Sociodemographic characteristics, clinical presentation, and hospital type and quality may play a role. The aim of this study was to examine the impact that certain factors may have on racial and ethnic differences in SMM.